Analysis of Summative Test at First Grade of SDIT Raudhatul Jannah Cilegon - Sintawati, Fairus; Wulandari, Ratih Ayu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2023)
This study aims to find out how the quality of the validity and reliability of the summative test questions in English class 1 at SDIT Raudhatul Jannah. The type of research used in this research is quantitative research because the data generated is in the form of numbers. The population used in this study were 30 students at SDIT Raudhatul Jannah. The sample used was 10 summative test questions. The data collection technique used was a documentation technique by photocopying the student grade data at SDIT Raudhatul Jannah. The data analysis technique used in this study was to use the SPPS version 26 program. Based on the results of the validity and reliability tests on this research instrument, namely summative test questions in English class 1 SDIT Raudhatul Jannah, it was found that the summative questions were prepared by the eye teacher. The lesson is valid with value and reliable or consistent to be used as a measuring tool in measuring student learning outcomes for a certain period. 6 out of 10 valid questions are measured using a significance number of 0.01 and have a reliability value of 0.644. This value exceeds the minimum limit of measurements using Cronbach Alpha if you want to be declared reliable, which is equal to 0.60. So, it can be concluded that the summative questions made by the English subject teacher at SDIT Raudhatul Jannah are valid and appropriate to use.